2022
DOI: 10.1038/s41380-022-01478-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and severity levels of inflammation and depression from childhood to young adulthood: a longitudinal cohort study

Abstract: Adverse childhood experiences (ACEs) are associated with depression and systemic inflammation in adults. However, limited longitudinal research has tested these relationships in children and young people, and it is unclear whether inflammation is an underlying mechanism through which ACEs influence depression. We examined the longitudinal associations of several ACEs across different early-life periods with longitudinal patterns of early-life inflammation and depression in young adulthood and assessed the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…For instance, it is possible that peripheral inflammation is only elevated for a few weeks or months following violence exposure. If this is the case, we are likely missing the window during which inflammation was elevated among these adolescents, resulting in the current study giving us the false impression that peripheral inflammation is not mechanistically important in connecting violence exposure with internalizing symptoms, a result which others have found (Iob et al, 2022). While the time course of inflammation following violence exposure has not been well characterized, human studies have confirmed increases in peripheral inflammation following acute stressors (Kautz et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…For instance, it is possible that peripheral inflammation is only elevated for a few weeks or months following violence exposure. If this is the case, we are likely missing the window during which inflammation was elevated among these adolescents, resulting in the current study giving us the false impression that peripheral inflammation is not mechanistically important in connecting violence exposure with internalizing symptoms, a result which others have found (Iob et al, 2022). While the time course of inflammation following violence exposure has not been well characterized, human studies have confirmed increases in peripheral inflammation following acute stressors (Kautz et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…Adverse childhood experiences (ACEs) (e.g., childhood abuse) occur in individuals from childhood to 18 years of age, differ in severity, and repeated over time (Hughes et al, 2017;Iob et al, 2022; LeMoult et al, 2020). ACEs impact children at stages in which they are vulnerable to biological, psychological, behavioral, and mental changes and issues (Herzog & Schmahl, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common mental disorder and one of the most important public health problems in the world. Increasing evidence shows a close connection between inflammation and depression [1,2]. The key to the influence of neuroinflammation on depression lies in the imbalance of the control and release of proinflammatory and anti-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%